Grievance Arbitration in Nova Scotia - Gilson, Clive; Gillis, L.P. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
This paper introduces research evidence which characterizes grievance arbitration in Nova Scotia from 1980 to 1986.